Theophylline affects three different potassium currents in dissociated rat cortical neurones. - Munakata, M (1993)
1. The effects of theophylline in pyramidal neurones acutely dissociated from the rat frontal cortex were investigated in the whole-cell configuration, using the nystatin-perforated patch-clamp technique. 2. Ten millimolar theophylline evoked triphasic responses: a small slow outward current (Iso), then a large transient outward current (Ito) and finally a slow sustained inward current (Isi). The reversal potentials of the three current components shifted 56-58 mV for a 10-fold change in extracellular K+ concentration, thereby indicating that all these current components were predominantly carried by K+. 3. Iso had no voltage dependence, whereas Ito showed a steep outward rectification. Iso was relatively resistant to tetraethylammonium (TEA) with an IC50 of 10 mM. Ito was susceptible to submillimolar TEA with an IC50 of 0.8 mM. 4. Isi was a net inward current mainly resulting from suppression of the M-current (IM). 5. These three current components had a distinct concentration dependence; in particular, Isi was evoked at a relatively lower concentration range. 6. Ito was not observed when the intracellular Ca2+ was chelated by 1,2-bis(O-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid (BAPTA) of 10 mM, using the conventional whole-cell recording configuration, whereas both Iso and Isi were retained but gradually diminished. 7. In Ca(2+)-free external solution, these responses were fully elicited by the first application of theophylline. However, Ito disappeared during successive applications and Iso, but not Isi, also decreased. Similar results were obtained in the presence of ryanodine. 8. Theophylline apparently affects three different kinds of K+ currents in rat cortical neurones. Both Iso and Ito depend on internal calcium mobilized from an intracellular Ca2+ store by theophylline, while Isi was not primarily mediated by a change in [Ca2+]i.